Method Development and Validation of Darifenacin in Rat Plasma by Liquid Chromatography-Tandem Mass Spectrometry: Application to a Pharmacokinetic Study. (27th November 2012) - Karavadi, Thejomoorthy; Challa, B. R.
Abstract : A selective, sensitive, and high-throughput liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) method has been developed and validated for the quantitation of darifenacin in rat plasma. Sample clean up involved liquid-liquid extraction (LLE) and used 100  μ L of rat plasma. Zorbax, SB C18, 4.6 × 75  mm, 3.5  μ m particle size analytical column using 10 mM ammonium acetate buffer (pH 5) and methanol (10 : 90, v/v) as the mobile phase was used. The parent → product ion transitions for the drug ( m/z 427.3 → 147.3) and IS ( m/z 431.4 → 151.2) were monitored on a triple quadrupole mass spectrometer, operating in the multiple reaction monitoring (MRM) and positive ion mode. The method was validated over the concentration range of 10.00–20000.00 pg/mL for darifenacin. The method was successfully applied into a pharmacokinetic study in rat plasma under fasting conditions.